PENGGUNAAN STATEGI AKTIF TIPE LEARNING STARS WITH A QUESTION (LSQ) DISERTAI HAND OUT PADAPEMBELAJARANBIOLOGI SISWAKELAS VIII SMP N 1 SASAK RANAH PASISIE KAB. PASAMAN BARAT TAHUN PELAJARAN 2012/2013 - Juniati, Juniati; Sudirman, Sudirman; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ The research is based on the lowest result of biology learning in the SMP N 1 Sasak Ranah Pasisie Â Kab Pasaman Barat, that doesin,t achieve of KKM. Because of the lowest student learning outcome in the Â learning process only uses a lecture and question and answer it, also the student become passive and minus participat in the study. This researdh is purpose to know the increasing of learking outcome biology of student that using strategy LSQ type and also Hand out on learning outcome of biology in VIIITh type this regearch is experiment, the population is all of student VIII class that student enrolled in 2012/2013 year education. The taking of sample with purposive sampling technigue, so we get the sample, that is VIII4 Â cclass as experiment class and VIII3 class as control class. The Â instrument that use is whiten test in objective question. The analysisi of dataÂ Â by uji-t. BasedÂ Â on score learning outcome, get the avereg of experiment is81,05 with deviation 7,91 and average of control class is 68,06 with deviation 12,29. By uji âtanalysis get the result t count (4,52) > ttable (1,67) that mean the hypothesis is accepted. Furthermore can be conclude that using LSQ type strategy also Hand out can increasing learning outcome student in SMP N 1 Sasak Ranah Pasisie 2012/2013 year educationÂ Â